2020
DOI: 10.1242/jeb.221499
|View full text |Cite
|
Sign up to set email alerts
|

A novel cylindrical overlap-and-fling mechanism used by sea butterflies

Abstract: The clap-and-fling mechanism is a well-studied, unsteady lift generation mechanism widely used by flying insects and is considered obligatory for tiny insects flying at low to intermediate Reynolds numbers, Re. However, some aquatic zooplankters including some pteropod (i.e. sea butterfly) and heteropod species swimming at low to intermediate Re also use the clap-and-fling mechanism. These marine snails have extremely flexible, actively deformed, muscular wings which they flap reciprocally to create propulsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Similar to the coiled shell species, the elongated shell species also exhibit forwardbackwards body pitching with every wing stroke, but the pitching amplitude seems to be less for the elongated shell species. For example, Karakas et al (2020) showed that C. atlantica has a pitching angle of 25 • , which is much less than pitching amplitudes previously measured for the coiled shell species L. helicina (up to 60 • ) and L. helicina antarctica (up to 110 • ; Adhikari et al, 2016;Murphy et al, 2016). The lower pitching amplitude of the elongated shell species makes sense because these shells have greater rotational drag and rotational inertia as compared to coiled shells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to the coiled shell species, the elongated shell species also exhibit forwardbackwards body pitching with every wing stroke, but the pitching amplitude seems to be less for the elongated shell species. For example, Karakas et al (2020) showed that C. atlantica has a pitching angle of 25 • , which is much less than pitching amplitudes previously measured for the coiled shell species L. helicina (up to 60 • ) and L. helicina antarctica (up to 110 • ; Adhikari et al, 2016;Murphy et al, 2016). The lower pitching amplitude of the elongated shell species makes sense because these shells have greater rotational drag and rotational inertia as compared to coiled shells.…”
Section: Discussionmentioning
confidence: 88%
“…Morton (1954) described the swimming behavior of Limacina retroversa qualitatively, and more recently Bergan et al (2017) conducted quantitative measurements of the swimming and sinking kinematics of the same species under the influence of elevated carbon dioxide, which alters shell properties. Karakas et al (2020) showed that the tropical thecosome Cuvierina atlantica uses its highly flexible parapodia in a cylindrical overlapand-fling mechanism twice during each stroke to generate lift. In the heteropods, Karakas et al (2018) discovered that, contrary to previous accounts (Lalli and Gilmer, 1989), the atlantiid heteropod Atlanta selvagensis does not let its shell passively hang beneath it as it swims but instead flaps its shell in coordination with its swimming fin in order to swim.…”
Section: Introductionmentioning
confidence: 99%
“…We recorded 27 free-swimming sequences from eight individuals ( B. vitrea ). We note that the camera system is also described in [36] and [37].…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured at 600 frames per second. This set-up is described in detail by Karakas, Maas & Murphy (2020), whose data are contemporary.…”
Section: Morphological Modelmentioning
confidence: 99%